Safety and efficacy of low-dose transarterial chemoembolization in the hepatocellular carcinoma patients with portal vein tumor thrombosis - Won-Gyom Choe; Yong-Gun Jo; Il-Jin Sim; Guk-Song Kim; Guang-Jin Chon; U-Il Song; Yong-Jin Pong (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of the study is to analyze the safety and efficacy of low-dose transarterial chemoembolization (TACE) for hepatocellular carcinoma (HCC) patients with portal vein tumor thrombosis (PVTT). Materials and Methods: Seventy-five HCC patients with PVTT, who were admitted to our hospital between 2011 and 2015 and underwent TACE, were analyzed. The safety and efficacy of low-dose TACE were evaluated. Results: The objective tumor response rate was 25.3%. The median overall survival time was 10.7 months (95% confidence interval [CI]: 8.2-13.2). The cumulative survival rates at 6, 12, 18, and 24 months were 65.3%, 44%, 17.3%, and 2.6%, respectively. Univariate analysis revealed that alpha-fetoprotein (heart rate [HR] = 1.307, 95% CI: 1.019-1.427,P < 0.05), Child-Pugh classification (HR = 2.984, 95% CI: 1.741-5.115, P < 0.001), PVTT (HR = 3.409, 95% CI: 2.745-4.512, P < 0.001), number of tumor (HR = 2.358, 95% CI: 1.956-3.375, P < 0.001), and size of tumor (HR = 2.301, 95% CI: 1.667-3.268, P < 0.001) were related with survival. In multivariate analysis, Child-Pugh classification (HR = 2.351, 95% CI: 1.256-4.215, P < 0.001), type of PVTT (HR = 2.749, 95% CI: 2.238-3.961, P < 0.001), number of tumor (HR = 1.795, 95% CI: 1.521-3.046, P < 0.001), and size of tumor (HR = 1.917, 95% CI: 1.379-3.057, P = 0.03) were independent predictive factors for survival rates. The incidence of complications due to procedures was 85.3%. Conclusion: The low-dose TACE may be considered selectively to HCC patients with PVTT. Child-Pugh classification, type of PVTT, number of tumor, and size of tumor were checked accurately before operation.